Engineering thermodynamics work and heat transfer - Rogers, Gordon (Pearson Education, 2006)
Engineering thermodynamics work and heat transfer / Rogers, Gordon. -- New Delhi: Pearson Education, 2006 536.7 R725e4 4th ed No. of Copies : 1